Forgotten Spaces, distinct places: Social transformation of urban space in Bogotá (1850-1880) (2014)
The purpose of this article is linked to some forms of recovery of social and urban spaces fallen into oblivion that are evident in the social transformation of urban space in Bogotá between 1850 and 1880.The following paper presents the preliminary results of the research entitled practices and social uses of water in Bogotá (1850-1888). The text links in first discussions about the understanding of the city as a drawing in space, moving to describe, the growth of the city, integrating its historical, social and cultural structuring.